MODE AND SUCCESS RATE OF DELIVERY OF LIVE BIRTHS FOLLOWING EMERGENCY CERVICAL CERCLAGE - SULTAN, S; FATIMA, SS; KHUBROO, . (Biological and Clinical Sciences Research Journal, 2024)
Cervical incompetence is a significant cause of second-trimester pregnancy loss and preterm birth. Emergency cervical cerclage (ECC) is a surgical intervention aimed at preventing these adverse outcomes by providing mechanical support to a weakened cervix. Objective: To evaluate the outcomes of emergency cervical cerclage in terms of mode of delivery and the success rate of live birth in patients presenting to a tertiary care hospital. Methods: This descriptive case series was conducted in the Department of Gynecology at Lady Reading Hospital, Peshawar, from May 2023 to November 2023. Ninety-six patients with cervical incompetence underwent ECC under aseptic conditions by a single surgical team using standard procedures. Data on the mode of delivery and fetal outcomes were collected. Patients were followed up bi-weekly for the first month, then monthly until delivery. Statistical analysis included descriptive statistics to summarize the outcomes. Results: Out of 96 patients, 61 (63.5%) had vaginal deliveries, while 35 (36.5%) had cesarean sections. The majority of pregnancies (67.7%) resulted in live births, whereas 32.3% of the cases resulted in fetal death. Conclusion: Emergency cervical cerclage is an effective intervention for women with cervical incompetence, capable of prolonging pregnancy and improving neonatal outcomes.